Benchmarking of outdoor activity facilities : an analysis of German hiking facilities and its implications to Finland - Amstein, Torsten (2015)
The health effects of regular physical activity play an integral part in the promotion of outdoor participation. Well-maintained and marketed outdoor facilities encourage in this regard people to be more active outside of their homes.